If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2(3y + -9) = -2(7y + -1) + 2y Reorder the terms: 6 + 2(-9 + 3y) = -2(7y + -1) + 2y 6 + (-9 * 2 + 3y * 2) = -2(7y + -1) + 2y 6 + (-18 + 6y) = -2(7y + -1) + 2y Combine like terms: 6 + -18 = -12 -12 + 6y = -2(7y + -1) + 2y Reorder the terms: -12 + 6y = -2(-1 + 7y) + 2y -12 + 6y = (-1 * -2 + 7y * -2) + 2y -12 + 6y = (2 + -14y) + 2y Combine like terms: -14y + 2y = -12y -12 + 6y = 2 + -12y Solving -12 + 6y = 2 + -12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12y' to each side of the equation. -12 + 6y + 12y = 2 + -12y + 12y Combine like terms: 6y + 12y = 18y -12 + 18y = 2 + -12y + 12y Combine like terms: -12y + 12y = 0 -12 + 18y = 2 + 0 -12 + 18y = 2 Add '12' to each side of the equation. -12 + 12 + 18y = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 18y = 2 + 12 18y = 2 + 12 Combine like terms: 2 + 12 = 14 18y = 14 Divide each side by '18'. y = 0.7777777778 Simplifying y = 0.7777777778
| x+(-8)=27 | | 84*(-36-x)=-2y | | 8x-4x+116=8x+72 | | 3x+2=10.4 | | -6z=8 | | w-16=72 | | 4.7x+46.5=23.7-6.7x | | -0.95(4x-2)=-0.2(3+6x) | | x-(x^2)=0.25 | | 5x+y=45 | | -12x+48=-4x+8 | | 4x+6x+2+8=3x+5+6x | | 4a+43=49+a | | 9x+12=3(x-2) | | 4x+6x+8=3x+5+6x | | 0=-16t^2+25t+220 | | 6x-3(4-x)=6 | | 7+26x=35+19x | | 7=5x-10 | | 7(-5+m)=42 | | -0+0=7 | | 1.5=4y+20.3 | | 7(x-2)=8-5y | | 5x+1x=22 | | ax-3=-2 | | y=x^2-4xy+y^2 | | 16n^2-100+24=0 | | 7x+6x-19=57-6x | | 2(0)-4(0)=12 | | 15x(-4)=-7+12x | | 4b^2-27b+18=0 | | -3.8x+1.9=6-1.2x |